THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE, EXCLUSIVE BREASTFEEDING, AND INFECTIOUS DISEASES WITH THE INCIDENCE OF WASTING IN TODDLERS AT UPTD PUSKESMAS JOHAN PAHLAWAN, WEST ACEH REGENCY, 2024. - Ratnatul Fadiah; Marniati; Laila Apriani Hasanah Harahap; Nasrianti Syam (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Wasting is a condition of thinness characterized by a weight-for-height index (W/H) with a Z-Score limit of <-2 SD. The problem in this study is the high incidence of wasting in 2022, which was 139 people (6.9%), and in 2023, it was 91 people (5.7%). These numbers are considered high because, according to WHO targets, the wasting rate should be <5%. The purpose of this study is to analyze the relationship between maternal knowledge, exclusive breastfeeding, and infectious diseases with the incidence of wasting in toddlers at UPTD Puskesmas Johan Pahlawan, West Aceh Regency. With a cross-sectional approach and a correlational design, this study employed a quantitative research methodology that examines the relationship between variables at the same time (point time approach). Seventy toddlers with wasting made up the study's population, and the total sampling approach was applied. The Chi-Square test was employed in both univariate and bivariate analysis.The findings demonstrated a strong correlation between the occurrence of toddler wasting and maternal knowledge (p=0.042), exclusive breastfeeding (p=0.028), and infectious illnesses (p=0.000). In conclusion, the value (p < α 0.05) indicates a correlation between the occurrence of wasting in toddlers, infectious illnesses, exclusive breastfeeding, and maternal knowledge. It is recommended that healthcare workers, especially at the health center, increase education for mothers of toddlers on the importance of exclusive breastfeeding and prevention of infectious diseases (diarrhea and ARI), and that mothers of toddlers can be more active in seeking information and participating in health counseling activities organized by posyandu/health centers to understand the importance of exclusive breastfeeding.